Shattering Hamlet's Mirror : Theatre and Reality - Carlson, Marvin, 1935- (Book collections on Project MUSE., 2016)
Theatrical playing, Hamlet famously averred, holds a mirror up to nature. But unlike the reflections in the mirror, the theater's images are composed of real objects, most notably bodies, that have an independent existence outside the world of reflection. Throughout Western theater history there have been occasions when the reality behind the illusion was placed on display. In recent years theaters in Europe and North America have begun calling attention to the real in their work-presenting performers who did not create characters and who may not even have been actors, but who appeared on stage as themselves; texts created not by dramatic authors but drawn from real life; and real environments sometimes shared by actors and performers and containing real elements accessible to both. These practices, argues Marvin Carlson, constitute a major shift in the practical and phenomenological world of theater, and a turning away from mimesis, which has been at the heart of the theater since Aristotle. Shattering Hamlet's Mirror: Theatre and Reality examines recent and contemporary work by such groups as Rimini Protokoll, Societas Raffaelo Sanzio, the Gob Squad, Nature Theatre of Oklahoma, and Foundry Theatre, while revealing the deep antecedents of today's theater, placing it in useful historical perspective. While many may consider it a post-postmodern phenomenon, the "theater of the real," as it turns out, has very deep roots.